Pengaruh E-Service Quality, E-Trust Terhadap E-Loyality Dengan Kepuasan Pelanggan Sebagai Variabel Intervening Pada Pengguna Jasa Transportasi Online Grab - M. Sulhan; Fani Dwi Rahma (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Current technological developments can develop very rapidly and this causes changes in people's lifestyles. With the presence of the internet, not only marketing- based businesses but also developing online transportation services such as Grab, which provides online transportation services to consumers. This needs to be considered as a service provider to maintain the loyalty of service users. This study aims to determine the effect of e-service quality and e-trust on e-loyalty through customer satisfaction on users of grab transportation services. This research was conducted in the community in the district Kecamatan Pandaan who uses grab transportation services in 2023. The data collection technique used is a questionnaire which is distributed online via Google Form. The selection of the sample used in the study was 100 respondents using the purposive sampling method, which is a sampling technique in which the people selected as samples are in accordance with the purpose of conducting research on data management, this research was conducted using the path analysis method (Path Analysis). Based on the results of this study it can be seen that e-service quality has a positive and significant effect on satisfaction, e-trust has a positive and significant effect on satisfaction, e-service quality has a positive and significant effect on e- loyalty, there is no significant relationship between e-trust directly to e-loyalty, and satisfaction has a positive and significant effect on e-loyalty